Towards a biblical model of Pentecostal prophetic preaching - Martin, Lee Roy (Verbum et ecclesia, 2016)
The growth and diversity of Pentecostalism has produced questions regarding appropriate methods for Pentecostal preaching. Increasing educational levels among Pentecostal pastors have caused many of them to move to more mainline Protestant approaches to preaching. This article, although allowing for diverse models of preaching, calls for an appreciation of Pentecostal approaches to preaching and suggests the appropriation of a biblical model of prophetic preaching. A paradigm for prophetic preaching emerges through an examination of biblical prophetic ministry as it intersects with Pentecostal practice. It is suggested that a contemporary model of Pentecostal prophetic preaching can be informed by the biblical models.Intradisciplinary and/or interdisciplinary implications: This study suggests intersections between biblical studies, historical theology, homiletics, and contemporary culture. It is argued that Pentecostal preaching should be based upon biblical models, while taking into consideration historical and cultural contexts. This work integrates the disciplines of biblical studies, practical theology, homiletics, and Pentecostal worship studies. Results from the biblical study of the prophets suggest that contemporary Pentecostal homiletical theory should entertain a model of prophetic preaching that emulates the goals and methods of the biblical prophets. The Pentecostal preaching tradition continues to offer valuable insights into effective preaching models; therefore, Pentecostal homiletics should not be based entirely upon western Protestant models of preaching.Keyword: Preaching; Homiletics; Pentecostalism; Prophecy